Massively Parallel Sequencingof the Filaggrin Gene Reveals an Association Between FLG Loss-of-function Mutations and Leprosy - Wenhao Shi; Zihao Mi; Zhenzhen Wang; Huimin Zhang; Na Wang; Zhe Wang; Bowen Zhang; Qianqian Xia; Yueqian Yu; Gongqi Yu; Lele Sun; Xian Fu; et al. (Medical Journals Sweden, 2020)
Filaggrin, encoded by the FLG gene, plays a crucial role in the barrier function of epidermis, but the association between FLG loss-of-function mutations and infectious skin diseases has not been systematically studied. FLG coding sequences from 945 patients with leprosy and 916 healthy controls were captured and enriched using an array-based high-throughput system, and subjected to next-generation sequencing. The loss-of-function mutations found were further validated by Sanger sequencing. A total of 21 loss-of-function mutations were found in 945 patients with leprosy, with a carrier rate of 17.53%, while the prevalence of these mutations in 916 healthy controls was 14.77%, which was significantly lower than in patients. Two individual FLG loss-of-function mutations (K4022X and Q1790X) were found to be significantly associated with leprosy. These results suggest a possible role for filaggrin in defending against leprosy pathogens.